Molecular cloning and DNA sequence analysis of a diphtheria tox iron-dependent regulatory element (dtxR) from Corynebacterium diphtheriae. - Boyd, J (1990)
Although the structural gene for diphtheria toxin, tox, is carried by a family of closely related corynebacteriophages, the regulation of tox expression is controlled, to a large extent, by its bacterial host Corynebacterium diphtheriae. Optimal yields of tox gene products are obtained only when iron becomes the growth-rate-limiting substrate. Previous studies suggest that regulation of tox expression is mediated through an iron-binding aporepressor. To facilitate molecular cloning of the tox regulatory element from genomic libraries of C. diphtheriae, we constructed a tox promoter/operator (toxPO)-lacZ transcriptional fusion in Escherichia coli strain DH5 alpha. We report the molecular cloning and nucleic acid sequence of a diphtheria tox iron-dependent regulatory element, dtxR, and demonstrate that expression of beta-galactosidase from the toxPO-lacZ fusion is regulated by dtxR-encoded protein in an iron-sensitive manner. In addition, we show that expression of the toxPO-lacZ fusion is not affected by the E. coli iron-regulatory protein Fur and that the dtxR protein does not inhibit expression of fur-regulated outer-membrane proteins.